Beyond the Boy Scout's sleeve: a personal review of ethical certification. (1st February 2019) - Wright, Simon
Abstract : This article reviews the history of third-party ethical certification of food and drink, concentrating mainly on organic and Fairtrade. The strengths and weakness of the approaches taken to date are reviewed. The author includes his personal experience of such schemes gained over the last thirty years. From this, he concludes that third-party certification has not delivered sufficient benefits to producers. He notes the challenge posed by new schemes designed and owned by large food processors and multiple retailers. The article concludes that it may be better to think of third-party certification as a first step rather than a destination.